2004
DOI: 10.1152/ajpheart.01143.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning and morphine attenuate myocardial apoptosis and infarction after ischemia-reperfusion in rabbits: role of δ-opioid receptor

Abstract: We examined whether ischemic preconditioning (IPC) attenuates ischemia-reperfusion injury, in part, by decreasing apoptosis and whether the delta-opioid receptor (DOR) plays a pivotal role in the regulation of apoptosis. Rabbits were subjected to 30-min coronary artery occlusion (CAO) and 180 min of reperfusion. IPC was elicited with four cycles of 5-min ischemia and 10-min reperfusion before CAO. Morphine (0.3 mg/kg iv) was given 15 min before CAO. Naloxone (Nal; 10 mg/kg iv) and naltrindole (Nti; 10 mg/kg iv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…This finding is in agreement with those of Okubo et al who reported a ␦-opioid receptor-mediated effect against myocardial apoptosis in a rabbit model of ischemia-reperfusion injury (Okubo et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with those of Okubo et al who reported a ␦-opioid receptor-mediated effect against myocardial apoptosis in a rabbit model of ischemia-reperfusion injury (Okubo et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Both DNA fragmentation and infarct size were significantly decreased after prolonged ischemia and reperfusion in the preconditioned rat and rabbit heart in vivo [14,33,34]. Moreover, a direct correlation between myocardial infarct size and internucleosomal DNA fragmentation was reported [33].…”
Section: Discussionmentioning
confidence: 94%
“…Activation of cardiac G-protein coupled delta opioid receptors (DOR) induces an intracellular kinase pathway in which activation of mitochondrial ATP-sensitive K + -channels seem to play an important role [8][9][10]. In addition, DOR activation triggers different mechanisms at multiple levels to stabilize homeostasis, to increase pro-survival signaling and antioxidative capacity, and to stimulate the growth of neonatal rat ventricular myocytes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%